Quality and Quantity of Corporate Disclosure by NZ Listed Companies after Implementing IASs and IFRSs - Jamal Roudaki (Journal of Accounting, Business and Management (JABM), 2011)
The main objective of International harmonisation and more recent accounting standard convergence is the enhancement of quality and quantity of financial accounting reporting internationally and locally. To assess the determinants and consequences of heterogeneity in corporate disclosure following international harmonisation/ convergence, this paper compares prior and posts mandatory adaptation of IASs and IFRSs in the New Zealand (NZ) listed environment. NZ has formally adopted International Accounting Standards (IASs) from the beginning of 2007 while voluntary adoption has been in place from bout 2003. This paper investigates the effect of the IASs and IFRSs on the quality and quantity of financial reporting by NZ listed companies when classified by dependent variables of size, industry, profitability, sustainable growth rate, international listing status and auditor type. In particular this paper examines whether applying the IASs and IFRSs have enhanced accounting disclosure of financial, non-financial, and strategic information provided by NZ listed companies.